2006
DOI: 10.1007/s10661-006-9506-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Enterococci from Seawater Samples: Assessment of Their Resistance to Antibiotics and Heavy Metals

Abstract: A hundred Enterococcus strains were isolated from seawater samples collected from coastal areas of Istanbul. Isolates were identified to the species level using standard biochemical tests specified by Facklam and Collins. The species distribution was as follows Enterococcus faecalis (96%), Enterococcus gallinarum (3%) and Enterococcus solitarius (1%). The resistance of bacteria to both heavy metals (zinc [Zn], iron [Fe], cadmium [Cd], chrome [Cr], cobalt [Co]) and antibiotics (ampicillin 10 microg [AP], penici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
21
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 32 publications
(51 reference statements)
4
21
5
1
Order By: Relevance
“…Similarly, Ben Said et al (2007) documented multiple polycyclic aromatic hydrocarbon-degrading bacterial strains isolated from Bizerte lagoon sediments, in Tunisia with capacity to resist some heavy metals and antibiotics. Unlike our isolates and those of Kimiran-Erdem et al (2007), the authors failed to show the concentrations of metals resisted, but this could be several orders-of-magnitude lower than we have reported (Table 3). Many researchers believed that combination of antibiotic and metal resistance may not be a fortuitous phenomenon (Nakahara et al 1977;Calomiris et al 1984), rather bacterial resistance against heavy metals appeared to be directly related to the presence of these elements as environmental contaminants (De Vicente et al 1990;Silva and Hofer 1993;Raja et al 2006).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ben Said et al (2007) documented multiple polycyclic aromatic hydrocarbon-degrading bacterial strains isolated from Bizerte lagoon sediments, in Tunisia with capacity to resist some heavy metals and antibiotics. Unlike our isolates and those of Kimiran-Erdem et al (2007), the authors failed to show the concentrations of metals resisted, but this could be several orders-of-magnitude lower than we have reported (Table 3). Many researchers believed that combination of antibiotic and metal resistance may not be a fortuitous phenomenon (Nakahara et al 1977;Calomiris et al 1984), rather bacterial resistance against heavy metals appeared to be directly related to the presence of these elements as environmental contaminants (De Vicente et al 1990;Silva and Hofer 1993;Raja et al 2006).…”
Section: Resultscontrasting
confidence: 99%
“…Heavy metal assayed were Cd 2+ , Hg 2+ , Co 2+ , Ni 2+ , and Cr 6+ particularly resistant to higher doses of cadmium (2-10 mM) and chromium (6-17 mM) while strains CA207Ni (P. aeruginosa) and AL06Ni were particularly resistant to over 15 mM of nickel with the former exhibiting resistance to 10 mM of cobalt (Table 3). In a relatively recent study, Kimiran-Erdem et al (2007) demonstrated dual resistance of 100 species of environmental enterococci to zinc, iron, cadmium, cobalt, chromium, and some antibiotics. However, the MICs recorded for these metals were much lower compared to over 100-fold concentrations that our isolates resisted.…”
Section: Resultsmentioning
confidence: 99%
“…The varying frequencies of antimicrobial resistance found in the present study was generally consistent with those of other studies toward bacteria from different natural environments including seawater [33][34][35].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of strong correlation between the densities of fecal indicators and the percentage of resistant isolates agrees with previous studies conducted in different localities around the world which showed positive correlations between the degree of pollution and bacterial resistance to antibiotics [12,35].…”
Section: Discussionsupporting
confidence: 91%
“…The presence of AR bacteria in coastal environments is a serious health risk and can contribute to the spread and evolution of antibiotic resistance, especially when resistance genes are carried on mobile genetic elements (MGE). However, little is known about the distribution of these genes among fecal bacteria from coastal marine environments, since most works report phenotypic studies in areas subjected to strong selective pressure (5,18,35).…”
mentioning
confidence: 99%